Adolescent frontal top-down neurons receive heightened local drive to establish adult attentional behavior in mice - Elisa M. Nabel (Nature Portfolio, 2020)
Frontal top-down cortical neurons implement top-down attentional control of sensory regions. The authors reveal adolescence as a developmental stage when frontal top-down neurons projecting from the anterior cingulate to visual cortex are functionally integrated into local excitatory circuitry.